Gharial Conservation in Orissa - Singh, Lala A. K. (Indian Forester, 1978)
Orissa is the only State to have all three Indian species of crocodilians viz., the Gharial (Gavialis Gangeticus), the Mugger or Marsh Crocodile (Crocodylus Palustris) and the Saltwater Crocodile (Crocodylus porosus), in their natural habitat. Gharial is one of the rarest crocodilians, endemic to the Indian subcontinent. The Satkoshia Gorge of the River Mahanadi in Orissa was once famous for its ghariaJ and mugger populations Indiscriminate hunting. Habitat alternation, nylon netting for fishing. Damming in the upper river and the local demand for eggs are some of the reations to bring down the crocodilian populations in the Mahanadi from March 1974 the Orissa Forest Department decided to protect ghariah and muggers in the Satkoshia Gorge. From 1975 with assistance from Government of India, Food and Agriculture Organisation of the United Nations and United nations Development Programme, Government of Orissa started a scheme at Tikerpada, beside the Satkosbia Gorge for studying (research) and conserving the Gharial. The operation of the scheme is based on "Grow and release" technique. Eggs are collected from nature aod incubated Under laboratory conditions, juveniles are reared to about a metre long and are reha bilitated in the Satkosbia Gorge of the Satkhoshia Gorge Sanctuary. To this date (September 1978) 156 gharials have been successCully reared at the Unit; out of which 72 have been rehabilitated in the river This project has also provided protection to other (autla in the saactuary and have provided employment to Munda tribes and local people Munda tribals have been refrained from their age-old practice of-egg eating, by providing work, employment and housing is some cases. Wide intereat have been created among public and tourists for crocodilians and other wildlife.